Gambaran Kondisi Lingkungan Fisik Ruang Rawat Inap di RS SUMBER HIDUP – GPM Kota Ambon - Andriana Ritje Nendissa; Donny J Pugesehan; Anastasia Arista Ohman (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2022)
The condition of the physical environment of the inpatient room can affect the psychological nature of the patient. The physical environment can be in the form of lighting, noise and temperature. The purpose of this study was to determine the conditions of noise, lighting and temperature in the inpatient room. The location of this research is in the inpatient room of Sumber Hidup Hospital – GPM Ambon City, in June 2021. This research is a descriptive study with quantitative methods. The sample used in this study is total sampling, which means that all members of the population are sampled, namely 31 rooms. Based on the Decree of the Minister of Health of the Republic of Indonesia No. 7 of 2019 concerning the environmental health of hospitals, it was found that the inpatient room at Sumber Hidup Hospital - GPM in Ambon City from the research results for Noise did not meet the 100% requirements with an average value of 60.9 dBA, meaning that the noise was more than the Standard Standard. Quality is 45 dBA. The lighting also does not meet the 100% requirements with an average value of 165.32 Lux, meaning that the lighting is less than the Quality Standard, which is 250 Lux. and the temperature does not meet the 100% requirements with an average value of 27.1 °C, meaning that the temperature is more than the Quality Standard, which is 22-23 °C. Conclusion: The location of the hospital close to the highway can affect noise. The lighting for the location of the room is blocked by natural light. The temperature of the ventilation system is inadequate and the air conditioner must be regularly maintained by IPSRS officers.Keywords: Hospitalization, Lighting, Noise, and Temperature